Hepatic-ductoplasty in pediatric choledochal cyst with hepatic duct stenosis: State of the art, treatment and systematic review - Jarruphong Noitumyae; Jarumon Amnuaypol; Chanokkamol Kiataramkul; Suranetr Chivapraphanant (Elsevier, 2023)
Background: The choledochal cyst associated with hepatic duct stenosis developed post-operative hepatolithiasis and complications. Objectives: To define state-of-the-art from the classification, treatment, and outcomes in systematic review and meta-analysis. Methodology: Three questions according to the finding, classification, preferred treatments, and outcomes were generated on published studies on PubMed, Scopus, Cochrane library database, Web of Science, and Google Scholar from January 1975 - April 2022. Result: Twenty published studies were included, and 517 patients(575 sites). The meta-analysis revealed the locations were the confluence of the left and right hepatic ducts 54.65%(141 sites), the left or/and the right hepatic duct 34.45%(89 sites), and the segmental intrahepatic duct 5.04%(13 sites). These characteristics included a membranous/septum appearance(47.2%) and a circumferential/relative stenosis(52.7%). The preferred treatments were the wide hilar Roux-en Y hepaticojejunostomy(67.00%), the excision of membranes/septum(33.00%), and the mixed hepatic-ductoplasty(33.82%)(open technique 51.38%, and laparoscopic technique 48.62%). The outcomes revealed hepatolithiasis 8/408(1.96%) in hepatic-ductoplasty compared to the normal anastomoses 26/109(23.85%), no statistical differences of meta analysis in anastomosis stricture(standard anastomosis 6.42%, open hepatic-ductoplasty 6.70% and 1.31% in laparoscopy). There was a higher bile leakage incidence in laparoscopy(10.04%) compared to open technique(0.056%). Conclusion: The hepatic-ductoplasty during the definite operation is effective. The characteristics and location can indicate the appropriate procedures. So, the hepatic-ductoplasty prevents hepatolithiasis or hepatic dilatation but increased anastomosis stricture. For laparoscopy, It's may decreased anastomotic stricture without persistent dilatation but increased minor bile leakage. Level of clinical evidence: level III-IV